Busca da superfície de ruptura crítica na análise tridimensional de estabilidade de taludes - SOARES, Patrícia Maria de Carvalho (2010)
The main objective is to develop, implement and evaluate a method to search for surfaces in order to determine the three-dimensional critical surface, corresponding to the lowest factor of safety of the embankment. They are also objectives of this study to evaluate the influence of the strength and elastic parameters the geometry of the slope safety factor and the 3D shape and position of the failure surface, as well as to evaluate the relationship between 2D and 3D safety factors. It was implemented an optimization routine in FORTRAN that performs the search for critical failure surface, whose safety factor is calculated by SAFE-3D program. The SAFE-3D program uses voltages coming from an elastic stress analysis performed by FlexPDE program, which uses the finite element method and provides the shear and normal stresses acting on the slope necessary to calculate the safety factor. For the analysis has been adopted as the ellipsoid shape of the rupture surface. The search method implemented examines safety factors obtained for a finite set of solutions and design variables as the coordinates of the center of the ellipsoid and the size of its three semi-axes. The search algorithm is implemented in successive tests of the factor of safety by SAFE-3D program, varying the position and dimensions of the ellipsoid for the determination of lower safety factor of slope. It was analyzed two examples of slopes, a symmetrical slope which varied the parameters of soil strength and the angle of the slope face and the other was the historic case of slipping Lodalen. The methodology implemented was successful in finding the critical failure surface, achieving consistency in results. The Poisson's ratio was very influential in the results of the safety factors of three-dimensional critical surfaces. It was also observed that there is less difference between the safety factors when keeping the shear stress unacceptable when these tensions are eliminated there is a closeness among the factors of safety.